The Effect of Corporate Commitment, Organizational Civilization Behavior, and Personal Compensation on Employee Performance with Work Achievement as a Moderator Study Hj. Fatimah Sulhan Hospital, Demak Regency - Aditya Angger Wibowo (Green Economics: International Journal of Islamic and Economic Education, 2026)
This study was carried out at RS Hj. Fatimah Sulhan in Kabupaten Demak, Jawa Tengah, which functioned as both the research site and the moderating context of the investigation. The research aims to examine how personal compensation, Organizational Citizenship Behavior (OCB), and organizational commitment influence employee work performance within the hospital environment. A quantitative research design was implemented, involving 150 employees selected as respondents through appropriate sampling procedures. Data were collected using structured questionnaires and subsequently analyzed using Structural Equation Modeling (SEM) with the AMOS software to test the hypothesized relationships among variables. The findings reveal that personal compensation, OCB, and organizational commitment each exert a positive and statistically significant impact on employee performance. These results indicate that fair and competitive compensation, strong voluntary work behaviors, and a high level of commitment to organizational goals collectively enhance productivity, service effectiveness, teamwork quality, and overall institutional performance in the healthcare setting.